Hubungan Kesiapan Menghadapi Perubahan dan Dukungan Organisasi terhadap Stres Kerja pada Aparatur Sipil Negara Dinas Kominfo Kabupaten Aceh Tenggara - Widya Putri Utami; Nur Aisyah; Syafruddin Ritonga (Mahesa Research Center, 2022)
The purpose of this study is to see: Relationship Readiness To Changes And Organizational Support with Work Stress in Civil Servants Of The Information Service Kutacane Southeast Aceh. This study was conducted on 99 civil servants with total sampling techniques. Data retrieval by scale method is the scale of readiness to changes, the scale of organizational support and the scale of work stress. Analyze data using Multiple Regression. The results showed; 1.There is a very significant relationship between readiness to change and organizational support with work stress. Based on the results of this study, it can be stated that the hypothesis proposed in this study is accepted. 2. There is a very significant negative relationship between readiness to changes and work stress. This means that the higher the readiness to changes, the lower the work stress. 3. There is a very significant negative relationship between organizational support and work stress. This means that the higher the organization's support, the lower the work stress. variable readiness to changes and organizational support contributed to work stress by 32.4%. Separately, readiness for change contributed 20.8% to high low work stress, while organizational support contributed 19.8% to high low work stress. From these results, it is known that there are still 67.6% influence of other variables on work stress, where other factors in this study are not seen, including factors of working conditions, ambiguity, interpersonal factors, career development and organizational structure.